Neuropathology of mitral valve prolapse in man and cardiopulmonary bypass (CPB) surgery in adolescent Yorkshire pigs - Sparks, D.Larry; Gross, David R; Hunsaker, John C (Neurobiology of aging, 2000)
We investigated the brains of non-demented individuals with mitral valve prolapse (MVP) and found evidence of Alzheimer-like lesions. This neuropathology consisted of premature presence of β–amyloid-containing senile plaques (SP) without increased prevalence of neurofibrillary tangles. Low levels of SP occurred in 20 to 45- year-old subjects with MVP, and much greater densities were observed in subjects between 45 and 62 years of age. We also investigated the brains of adolescent Yorkshire pigs undergoing cardiopulmonary bypass surgery and likewise found evidence of Alzheimer-like neuropathology. This took the form of intraneuronal accumulation of β–amyloid immunoreactivity and increasing numbers of Alz-50 immunoreactive neurons with reduced recovery of cardiac efficiency after the surgery. Based on prevailing concepts in Alzheimer’s disease, it is feasible to hypothesize that cognitive dysfunction occurring after cardiopulmonary bypass surgery with coronary artery grafting or valve repair/replacement is a functional sequela of AD-like neuropathology. This postulate is based on the premise that an individual seeking such surgery would have pre-existing, elevated AD-like neuropathology to start with. It is further coupled with the probability that these forms of cardiovascular surgery exacerbate the extent and progression of AD-like neuropathology.